Effect of zirconium substitution on the phase formation and microstructure of BaCeO3 - N. Osman,; I.A. Talib,; H.A. Hamid, (Universiti Kebangsaan Malaysia, 2010)
Polycrystalline compounds of Ba(Ce1-xZrx)0.95Yb0.05O2.975 (0.20 ≤ x ≤ 0.40) were prepared by the conventional solid state reaction method. All the samples exhibited the orthorhombic structure of BaCeO3. The particle size and morphology of the powdered samples were found to change gradually with Zr content. The sample with x=0.40 showed more agglomerates of about 10.0 μm in size, and the particles constituting the agglomerates were smaller than 1.0 μm. For the polished and etched pelleted samples, only the x=0.20 sample showed clear grain shapes with sizes in the range of 1.0 to 3.0 μm. By increasing the Zr content to more than 20 mol%, the grain sizes became less pronounced and smaller. The deficiency of Ba that caused the formation of a Ce, Zr and Yb-rich sample was detected by energy dispersive X-ray measurement. Ba deficiency was attributed to the loss of BaO during the calcination and sintering processes.